Biofilm formation by mercury resistant bacteria from polluted soil small-scale gold mining waste (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurfitriani S, Arisoesilaningsih E, Nuraini Y, Handayanto E. 2021. Biofilm formation by mercury resistant bacteria from polluted soil small-scale gold mining waste. Biodiversitas 23: 992-999. Small-scale gold mining has a major impact on living things and the environment due to mercury contamination. Bacteria are known to have a defense mechanism in mercury-contaminated soil. The biofilm produced by bacteria helps them survive and protect them from environmental stresses. This study aimed to find mercury-resistant bacteria capable of forming biofilms from mercury-contaminated soil in small-scale gold mining. Samples for bacterial isolation were mercury-contaminated soil from three gold processing sites in Lombok, Indonesia. The obtained mercury-resistant bacteria were tested to form biofilms on the media according to the test dose. The bacterial biofilms formed were observed, and each biofilm's adsorption capacity was measured. The three bacteria with highest adsorption values were identified molecularly using 16S rDNA. The results showed that most mercury-resistant bacteria were able to form biofilms at a dose of 25 ppm. However, only four bacteria were able to produce biofilms at a dose of 50 ppm. Biofilms of three bacteria had the highest adsorption values, ranging between 2.78-3.5. The three bacteria were identified as Bacillus toyonensis (JGT-F1), Burkholderia cepacia (PJT-K), and Microbacterium chocolatum (PJT-D). This study indicates that biofilm-producing bacteria are one of the remediation agents and can be used in mercury bioremediation.
Keywords: Bacterial biofilm, mercury-resistant bacteria, soil pollution, small-scale gold mining